2016
DOI: 10.1123/pes.2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and Muscle Tissue Oxygenation During Incremental Cycling in Male Adolescents Measured by Time-Resolved Near-Infrared Spectroscopy

Abstract: Near-infrared spectroscopy (NIRS) has long been used to measure tissue-specific O2 dynamics in exercise, but most published data have used continuous wave devices incapable of quantifying absolute Hemoglobin (Hb) concentrations. We used time-resolved NIRS (TR-NIRS) to study exercising muscle (Vastus Lateralis, VL) and prefrontal cortex (PFC) Hb oxygenation in 11 young males (15.3 ± 2.1 yrs) performing incremental cycling until exhaustion (peak VO2 = 42.7 ± 6.1 ml/min/kg, mean peak power = 181 ± 38 W). TR-NIRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
4
10
1
Order By: Relevance
“…In [18], the authors observed significantly higher relative SO 2 (r SO 2 ) at high intensity compared to rest, which is in the opposite direction of our extra-cerebral SO 2 . Non-significant changes in SO 2 measured with TD-NIRS in Ganesan et al [24] are consistent with our cerebral SO 2 . Furthermore, these studies were also compared with hemoglobin concentrations retrieved using our homogeneous model ( Table 5, Appendix A).…”
Section: Benefits Of the Techniquesupporting
confidence: 92%
See 3 more Smart Citations
“…In [18], the authors observed significantly higher relative SO 2 (r SO 2 ) at high intensity compared to rest, which is in the opposite direction of our extra-cerebral SO 2 . Non-significant changes in SO 2 measured with TD-NIRS in Ganesan et al [24] are consistent with our cerebral SO 2 . Furthermore, these studies were also compared with hemoglobin concentrations retrieved using our homogeneous model ( Table 5, Appendix A).…”
Section: Benefits Of the Techniquesupporting
confidence: 92%
“…2, the significant increase in cerebral HbR between 80% and rest was coherent with two studies [16,17]. Our results in HbO 2 and HbT were also consistent with a CW-NIRS study performed at normal (150 m) altitude [18], while they were not in agreement with significant increases observed between moderate and high exercise intensity compared to rest [16,17,24]. In [18], the authors observed significantly higher relative SO 2 (r SO 2 ) at high intensity compared to rest, which is in the opposite direction of our extra-cerebral SO 2 .…”
Section: Benefits Of the Techniquesupporting
confidence: 89%
See 2 more Smart Citations
“…The mean time response for muscle tissue deoxygenation is significantly faster in children than adults at the onset of high intensity exercise (Willcokcs, Williams, Barker, Fulford, & Armstrong, 2010). 13-17-year-old boys demonstrate significant changes in absolute hemoglobin concentrations and oxygenation in the exercising muscle during incremental cycling and post-exercise recovery (Ganesan et al, 2016). 9-year-old girls demonstrate an earlier change in [HHb] compared with same age boys during ramp incremental exercise (McNarry et al, 2015).…”
Section: Indroductionmentioning
confidence: 97%